ANALISIS PEMASARAN BERAS DI DESA BANGKIR KECAMATAN DAMPAL SELATAN KABUPATEN TOLITOLI - Nurhidaya, Nurhidaya; Hadayani, Hadayani; Lamusa, Arifuddin (AGROTEKBIS, 2017)
This study aims to determine the marketing channels, marketing margin, part of the price received by farmers and marketing efficiency. Respondents determined using simple random method (Simple Random Sampling) with 40 number of respondent farmers while the traders determined usingÂ  an assessment method (Tracing sampling) in order to obtain 2 traders, 1 wholesalersÂ  and 2 retailers. The analysis method used is the analysis of marketing. Marketing analysis results showed that rice marketing channel in the village distributed through two marketing channels i.e. (1) Farmers â Traders â Retailer â End Consumers and (2) Farmers â traders â wholesaler â retailer â end consumers. Rice marketing margin analysis on the first channel results is Mt = Rp 1,500/ kg and rice marketing margin on the second channel is Mt = Rp 2,000/ kg part of prices received by farmers in the first chnnel is 83.33% and part of prices received by farmers in the second channel is 78.94%, therefore the greatest price received by farmers is in the first channel. The first channel efficiency is 6.0%, while the second channel efficiency value is 8.6%. From the two the rice marketing channels, the first channel more efficient than second channel.Â